Adaptability of Islamic Jurisprudence in Hajj: Comparative Study of Four Madhhabs in Technological Era - Abdillah (Al-Risalah, 2025)
This study aims to examine how Islamic jurisprudence, particularly the four major Sunni schools (Hanafi, Maliki, Shafi’i, and Hanbali), adapts to contemporary transformations in Hajj practices. It explores the extent to which traditional rulings evolve in response to technological innovations, health protocols, and gender-related developments, especially the participation of women without a mahram. Employing a qualitative-comparative approach, this research analyzes classical fiqh texts alongside contemporary fatwas, official guidelines, and academic commentaries. Through the lens of ijtihad and maqāṣid al-sharī‘ah, the study critically assesses scholarly interpretations on issues such as electronic identification, mobile applications, surveillance systems, health measures, and modern transportation. Findings reveal that all four Sunni schools demonstrate varying degrees of flexibility in accommodating modern realities. While the Hanafi school maintains traditional restrictions in certain areas, the Maliki, Shafi’i, and Hanbali schools generally permit adaptations that prioritize safety, public interest, and ease of religious observance. Jurists increasingly accept the use of technology and revised travel norms, including the allowance for women to perform Hajj without a mahram under safe conditions. This research offers a comprehensive comparative analysis that integrates classical jurisprudence with modern contextual needs. It contributes to the growing discourse on how Islamic law remains relevant by evolving within the framework of maqāṣid al-sharī‘ah, particularly in a globalized and technologically advanced society. The study underscores the importance of dynamic legal reasoning in preserving both the sanctity and accessibility of Hajj. It supports the legitimacy of using ijtihad and contextual interpretation in contemporary Islamic legal thought, providing guidance for religious authorities, policymakers, and Muslim communities navigating modern pilgrimage challenges